2016
DOI: 10.5194/tc-10-1679-2016
|View full text |Cite
|
Sign up to set email alerts
|

Greenland annual accumulation along the EGIG line, 1959–2004, from ASIRAS airborne radar and neutron-probe density measurements

Abstract: We test radar-derived accumulation rates sensitivity to density using modeled density profiles in place of NP densities. ASIRAS radar layers combined with Herron and Langway (1980) model density profiles (ASIRAS-HL) produce accumulation rates within 3.5 % of ASIRAS-NP estimates in the dry snow region. We suggest using Herron and Langway (1980) density profiles to calibrate radar layers detected in dry snow regions of ice sheets lacking detailed in situ density measurements, such as those observed by the Operat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…For instance, current model horizontal resolution of RACMO2.3 (11 km) is insufficient to resolve the individual, low-lying outlet glaciers of the GrIS where runoff is especially large; as a result RU increases when the 11 km field is statistically downscaled to 1 km resolution (Nöel et al, 2016). This unresolved mass loss is likely in part error-compensated by snowfall in RACMO2.3 being underestimated in some regions of the ice sheet (Overly et al, 2016). In a recent study, it was moreover demonstrated that while RACMO2.3 tends to time drifting snow events well, the model likely overestimates drifting snow transport and therewith drifting snow sublimation .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, current model horizontal resolution of RACMO2.3 (11 km) is insufficient to resolve the individual, low-lying outlet glaciers of the GrIS where runoff is especially large; as a result RU increases when the 11 km field is statistically downscaled to 1 km resolution (Nöel et al, 2016). This unresolved mass loss is likely in part error-compensated by snowfall in RACMO2.3 being underestimated in some regions of the ice sheet (Overly et al, 2016). In a recent study, it was moreover demonstrated that while RACMO2.3 tends to time drifting snow events well, the model likely overestimates drifting snow transport and therewith drifting snow sublimation .…”
Section: Discussionmentioning
confidence: 99%
“…1; Machguth et al, 2016) and at 182 sites in the accumulation zone (white dots in Fig. 1) including snow pits, firn cores (Bales et al, 2001(Bales et al, , 2009, and airborne radar measurements (Overly et al, 2016). We exclusively selected measurements that temporally overlap with the model simulation .…”
Section: Observational Datamentioning
confidence: 99%
“…cloud physics (Van Tricht et al, 2016) and turbulent fluxes (Noël et al, 2015;Fausto et al, 2016). Therefore, considerable efforts have been dedicated to evaluating and improving polar RCM output in Greenland (Ettema et al, 2010b;Van Angelen et al, 2013b;Lucas-Picher et al, 2012;Fettweis et al, 2017;Noël et al, 2015;Langen et al, 2017), using in situ SMB observations (Bales et al, 2001(Bales et al, , 2009van de Wal et al, 2012;Machguth et al, 2016), airborne radar measurements of snow accumulation (Koenig et al, 2016;Overly et al, 2016;Lewis et al, 2017) and meteorological records (Ahlstrøm et al, 2008;Kuipers Munneke et al, 2018;Smeets et al, 2018), including radiative fluxes that are required to close the ice sheet surface energy balance (SEB) and hence quantify surface melt energy.…”
Section: Introductionmentioning
confidence: 99%
“…1). Accumulation observations were derived from 182 sites including snow pits and firn cores (Bales et al, 2001(Bales et al, , 2009) as well as airborne radar measurements (Overly et al, 2016) (white dots in Fig. 1).…”
Section: Ablation and Accumulation Measurementsmentioning
confidence: 99%